Open source audio as a teaching tool to develop the speaking skill in students of sixth grade at unidad educativa Rubira, Salinas, Santa Elena province, 2015-2016. - Villón Chancay, Marlene del Rosario (2016)
The necessity of communicating with people from several nations of the world increased due to changes in diverse aspects, such as, businesses, science, technology, academic studies, and others. The problem is that people have different languages; hence, it also increased the need of having a common international language. English as occupied this place; it is one of the most spoken languages around the world. However, lots of people have serious problems at the moment of speaking in English due to various reasons. In Ecuador, people need to use this language since it is a touristic country which is visited by several English foreigners per year. The proposal Open Source Audio as a teaching tool in order to develop the speaking skill was implemented at Unidad Educativa “Rubira”, located in Salinas, from the Santa Elena Province and it was developed following different methods, applying diverse techniques and instruments for collecting information. Thus, this research applied the quantitative method since it allowed the application of surveys in the thirty-six students from sixth grade; all this information was included by using charts and statistical graphics in order to illustrate the way in which students responded survey questions. Moreover, this investigation applied the qualitative method since it was possible interview different people, such as, principal and English teachers at Unidad Educativa “Rubira”, and one English language teaching expert. Finally, the observation technique was applied using an observation guide in order to evaluate the strategies that teacher applies in the development of an English language lesson; this allowed realizing that students were being instructed in a non-appropriated way since it was not any motivational activity during the speaking instruction.